Production efficiency through downtime analysis of packaging process(case study: Cargill Indonesia Plant) - Arief Rahmawan; Tian Nur Ma’rifat; Ahmad Baiquni Fariz Azka (Universitas Darussalam Gontor, 2020)
Cargill Indonesia Plant Gunung Putri is a company engaged in the processing of animal feed for chickens. In the production process, there is one stage in which the operation uses a machine and is assisted by continuous human labor, namely in the packing process. However, due to the high value of downtime in the process, the value of effectiveness and efficiency in the production process decreased so that the amount produced did not match the target. This study aims to analyze the causes of downtimein the packing process by providing recommendations for improvements in the form of making an operation process map. The research object focuses on two workstations on the animal feed production floor. The results showed that the biggest contribution of downtime was stamp label activity, pallet change, data input and communication activities between supervisors and workers. Several recommendations were proposed, including procuring automatic labeling machines, relocating packing stations and labeling equipment and making parallel work on stamp labeling activities, inputting data, picking up sacks and setting machines